The mechanism of vascularized lymph node transfer for lymphedema: natural lymphaticovenous drainage - Cheng, Ming-Huei; Huang, Jung-Ju; Wu, Chih-Wei; Yang, Chin-Yu; Lin, Chia-Yu; Henry, Steven L.; Harhaus-Wähner, Leila (Plastic and reconstructive surgery, 2014)
Background: Vascularized lymph node flap transfer for the treatment of upper and lower limb lymphedema has had promising results. This study was performed to investigate the mechanism of lymph drainage of a vascularized lymph node flap both experimentally and clinically. Methods: In the experimental study, 18 Sprague-Dawley rats were used to create 36 flaps, either a groin lymph node flap or an abdominal cutaneous flap that did not contain lymph nodes. Indocyanine green dye was injected into the edge of 12 lymph node flaps, directly into a lymph node of 12 lymph node flaps, and into the edge of 12 cutaneous flaps. In the clinical study, an identical study design was used, with 24 vascularized lymph node flaps and 12 cutaneous flaps not containing lymph nodes. Results: Experimentally, fluorescence was detected in the pedicle vein after a mean latency period of 153 ± 129 seconds when the edge of the lymph node flap was injected and 12.8 ± 8.1 seconds when the lymph node was directly injected. Fluorescence was not detected in the pedicle vein of the cutaneous flaps (p < 0.01). Clinically, fluorescence was detected in the pedicle vein after a mean latency period of 346 ± 249 seconds when the edge of the lymph node flap was injected and 23.5 ± 27.1 seconds when the lymph node was directly injected. Fluorescence was not detected in the pedicle vein of the cutaneous flaps (p < 0.01). Conclusion: The vascularized lymph node flap drains lymph into the pedicle vein, both experimentally and clinically. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.
Gesehen am 27.10.2020